Desain Mesin Penyedia Obat di Masa Pandemi Covid-19 untuk Kegiatan Pengabdian Masyarakat di Kelurahan Jatimelati Pondok Melati Bekasi - Mauludi Manfaluthy; Devan Junesco; Muhammad Assadullah (Jurnal Abdimas ADPI Sains dan Teknologi, 2022)
The surge in positive cases of Covid-19 in Indonesia has increased the demand for medicines and vitamins. As a result, many residents visited the village health center, pharmacies, and drugstores to buy medicine or vitamins to boost their body's immunity during a pandemic. health protocols that limit room capacity result in queues of buyers snaking which can lead to the potential for new infections. The World Health Organization (WHO) itself urges people to implement contactless payments, by using e-money or using electronic payments and avoiding touching touchless devices. This research is a continuation of the activity plan for Community Service at the Jatimelati village health center Pondok Melati Bekasi. Machines providing medicines that accommodate contactless and face-to-face contact with officers are deemed necessary to meet the needs of medicines and vitamins as a complement to machines providing medicines and vitamins so that people can get them more easily during and after the pandemic. In this study, this drug supply machine is equipped with a payment system using a balanced RFID card such as e-money and is also integrated with the website to facilitate monitoring of drug stock availability.